Psychologische Belastbarkeit von Jugendliсhen in einer sich verändernden Welt - Bruk, Zhanna; Kuchterina, Galina (International Dialogues on Education Journal, 2017)
The problem of overcoming difficult, stressful situations in today’s fast-changing society deserves attention since the success of its solution depends on teenagers’ intellectual, emotional and personal well-being. The ability to cope with life’s difficulties is characterized by personality traits and individual behavior patterns which are being actively developed at this age. One of such traits is vitality that determines a person’s ability to withstand a stressful situation, while maintaining the internal balance without reducing the success of the activities. The teenagers’ reactions to non-standard crisis situations depend on the conscious or subconscious choice of the models of protective and coping behavior. The article presents the results of the studies on the relation between the general index of teenagers’ vitality and protective strategies of coping behavior which they need to overcome stressful situations. The term “resilience” in our study includes adolescent’s vitality, their use of a variety of protective strategies of coping behavior. The study involved 144 teenagers (66 boys and 78 girls) from the 8-th grade, aged 14-15 years on the basis of the secondary school № 5, Tyumen, Russia. To test the hypotheses of the study the diagnostic data of adolescents resulting from the application of methods “Vitality” by S. Muddy (adaptation D.A. Leontiev, E.I. Tales); questionnaire “Index lifestyle” R. Plutchik (adaptation L.I. Wasserman, O.F. Eryshev, Klubova E.B.); questionnaire “Strategies for overcoming stressful situations,” S. Hobfoll (adaptation N. Vodopyanova) were analyzed using Pearson’s correlation coefficient. Teenagers’ general vitality is closely linked with the psychological defense mechanisms such as negation, regression, replacement and rationalization, as well as coping strategies such as avoidance. The study has found no correlation of vitality with prosocial and antisocial actions in stressful situations. Therefore, the study of individual human resources, and resilience and vitality, in particular, is of particular importance today.